Tanggung Jawab Emiten Yang Delisting Terhadap Para Pemegang Saham Di Pasar Modal - Wahdania, Sheila; Ganefi; Sofyan, Tito (Jurnal Ilmiah Kutei, 2023)
The advanced development of science and technology also has an impact on the development of a country's economy. The rapid development of the economy, especially in the financial sector, has made the capital market a source of financing for a company. Companies that enter the capital market are public companies that have made public offerings on the stock exchange. One of the risks in selling on the stock exchange through the capital market is delisting. This study aims to analyze the legal basis for delisting and the responsibilities of delisted issuers to investors in the capital market. The research method used in this study is a normative juridical research type and uses statutory and conceptual approaches. The results of the study show that the responsibilities of issuers who are delisted to investors in the capital market are regulated in the Capital Market Law, the Limited Liability Company Law and the Financial Services Authority Regulations which regulate the mechanism for repurchasing shares and the legal protection given to investors for acts of negligence rather than issuers, in the form of sanctions given to forced delisting issuers. However, the regulation still does not explain in detail what form of responsibility the issuer should provide for the losses experienced by investors. In order to overcome these problems, clear arrangements are needed regarding the form of issuer's responsibility and legal protection for investors due to delisting, so as to provide legal certainty for investors.